Electronic Cigarettes and Vaping in Adolescents: State-of-the-Art (2024)
ABSTRACT: Electronic cigarettes (EC) constitute a subset of electronic nicotine delivery systems (ENDS), designed to mimic conventional cigarettes (CC). These devices heat a liquid solution containing flavors, nicotine, or tetrahydrocannabinol to generate an aerosol that is inhaled, garnering significant interest among adolescents from early ages, accompanied by an increased incidence of usage and a lack of awareness regarding their effects, fueled by advertising campaigns portraying EC as innocuous. EC induce pulmonary, gastrointestinal, cardiovascular, neurological, cutaneous, and other complications, ranging from mild to fatal. The emergence of electronic cigarette or vaping product use-associated lung injury (EVALI) was first reported in 2017, with a subsequent surge in cases prompting numerous alerts in the United States. Despite public health measures restricting the sale of specific EC or vaping products in certain countries, adolescent consumption remains inadequately controlled. It is imperative for pediatricians and primary care physicians to understand the implications of vaping, facilitating timely preventive and therapeutic interventions.